Effect of fatigue on functional stability of the knee: Particularities of female handball players - Gillot, T.; L'Hermette, M.; Garnier, T.; Tourny-Chollet, C. (International Journal of Sports Medicine, 2019)
The risk of anterior cruciate ligament injury in female handball players is high. Fatigue of active stabilizers and increases in joint laxity are often mentioned in the literature as causal factors. However, no studies have been carried out on this population. Our objective is to determine the effect of muscle fatigue on active and passive knee stability in female handball players. This prospective study assessed tibiofemoral joint laxity, as well as hamstring and quadriceps strength, before (Tinitial), during and 3?min after (Tfinal) an isokinetic fatigue protocol (25 repetitions of knee flexion / extension at 180°.s-1). Laxity values (slope of the displacement-load curve and anterior tibial translation) were measured using a GNRB-Rotab® arthrometer; torque values were measured at specific joint angles and peak muscle torque using an isokinetic dynamometer. Nineteen women (20.9±2.4 years, 62.0±4.9 kg, 166±5 cm) were included. Normalized peak torque decreased significantly between the first three and last three repetitions of the fatigue protocol (p<0.0001, ES=3.2 and 3.2). Slope of the displacement-load curve and anterior tibial translation, functional and conventional ratios did not change significantly between Tinitial and Tfinal. Active and passive markers of knee stability were not altered by a fatigue protocol in female handball players, suggesting these players have a large capacity for recovery. These results suggest that muscle strengthening to prevent ACL injury in female handball players may be inappropriate.